Global instability and the development project: is the twenty-first century different? - Jayati Ghosh (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2018)
Despite a few pockets of relatively fast expansion, overall deficiency of demand characterises the world economy. The external stimulus provided by the US is declining; Europe's net impact is negative because of the emphasis on generating current-account surpluses. While China is already a significant global economic player, it cannot adequately counter the effect of this reduced impetus from the major developed countries. Much of the developing world is relying on unsustainable debt-driven bubbles in the financially liberalised environment to generate economic recovery. Sustaining the development project will require countries to shift from export-oriented growth to more reliance on domestic demand through wage and employment increases.
Keywords: B50; F40; O11; 330; world economy; financial instability; global trade; development